Activation of the transcription factor NF-κB in the rat air pouch model of inflammation. Issue 4 (1st April 2000) - Ellis, L; Gilston, V; Soo, C C-Y; Morris, C J; Kidd, B L; Winyard, P G
Abstract : OBJECTIVE: To investigate the activation of NF-κB in the carrageenan rat air pouch model of inflammation in a time course experiment, and the effect of dexamethasone on NF-κB activation. METHODS: Air pouch tissue treated with carrageenan (inflamed tissue) was obtained from rats killed at days 1, 2, 3, 6, 14, 21, 28 and 35 after carrageenan challenge. Tissue was also taken from non-carrageenan treated pouches (non-inflamed tissue) at day 3, and from inflamed tissues treated with dexamethasone. Tissue sections were wax embedded and stained with an "activity specific" monoclonal antibody raised against the nuclear localisation signal (NLS) of the p65 sub-unit of NF-κB. RESULTS: Cells containing activated NF-κB were detected in the intimal and sub-intimal regions of the air pouches as early as day 1. There was a significant increase in cells staining for activated NF-κB as the inflammation progressed. Initially cells staining were more prominent in the intimal versus sub-intimal region (p<0.001 for day 1) and at later time points the pattern was reversed (p<0.001 for day 6). There was a significant reduction in the number of cells staining for activated NF-κB in tissue taken from dexamethasone treated rats, compared with inflamed pouches alone (p<0.001). At no time point was positive staining for activated NF-κB observed in blood vessels. CONCLUSIONS: Activated NF-κB is present in the inflamed air pouch and the activation is associated with the inflammatory response to carrageenan. Treatment with dexamethasone resulted in reduced numbers of cells staining for activated NF-κB.